Maternal Mortality Analysis Through AMP-SR Review in East Kalimantan Province, Indonesia, 2023–2024 - Ari Utari; Ratno Adrianto; Ike Anggraeni Gunawan (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Maternal mortality remains a major public health challenge in East Kalimantan Province, despite a decline in reported cases from 83 deaths in 2023 to 74 deaths in 2024. Objective : This study aimed to describe the pattern of maternal deaths based on maternal characteristics, timing and place of death, and to analyze preventable factors through the Audit Maternal Perinatal Surveillance and Response (AMP-SR) approach. Research Methods/ Implementation Methods : A descriptive-analytic case series design was applied using secondary data from the East Kalimantan Maternal Perinatal Death Notification (MPDN) database for 2023–2024. Results : The results revealed that more than 51% of deaths occurred during the postpartum period and 77% took place in hospitals, indicating the predominance of Delay 3 (delays in receiving adequate care). Analysis of modifiable factors showed that most deaths were preventable through improvements in the quality of obstetric services, increased antenatal care (ANC) compliance, and strengthened referral and postnatal follow-up systems. The major risk factors included delays in family decision-making, weak interfacility referral coordination, and inadequate case management at referral hospitals. Conclusion/Lesson Learned : These findings highlight that reducing the Maternal Mortality Ratio in East Kalimantan requires the completion of 100% AMP-SR case reviews, the strengthening of Postnatal Care (PNC) implementation, and the enhancement of Emergency Obstetric and Neonatal Care (EmONC) capacity across all levels of healthcare facilities.